The Pride and Joy of Engineering? The Identity Work of Male Working-Class Engineering Students. Issue 3 (2nd September 2019) - Danielsson, Anna T.; Gonsalves, Allison J.; Silfver, Eva; Berge, Maria
Abstract : In this article, we explore the identity work done by four male, working-class students who participate in a Swedish mechanical engineering program, with a focus on their participation in project work. A focus on how individuals negotiate their participation in science and technology disciplines has proven to be a valuable way to study inclusion and exclusion in such disciplines. This is of particular relevance in engineering education where it is widely argued that change is needed in order to attract new groups of students and provide students with knowledge appropriate for the future society. In this study we conceptualized identity as socially and discursively produced, and focus on tracing students' identity trajectories. The empirical data consists of ethnographic field notes from lectures, video-recordings of project work, semi-structured interviews, and video-diaries recorded by the students. The findings show that even though all four students unproblematically associate with the 'technicist' masculinity of their chosen program it takes considerable work to incorporate the project work into their engineering trajectories. Further, 'laddish' masculinities re/produced in higher education in engineering also contribute to a 'troubled' identity trajectory for one of the interviewed students.